The Importance of Wetlands for the Conservation of Birds in Tigray National Regional State (Northern Ethiopia) - Kalayu Mesfin; Alembrhan Assefa; Weldemariam Tesfahunegny (International Journal of Zoology)
Many birds use wetland habitats for all or part of their lives. This study was conducted to investigate the significance of wetlands and associated habitats for bird conservation in the central zone of Tigray, northern Ethiopia, from June 2022 to May 2023. The point count method was used to study the bird assemblage structure and diversity. The Shannon–Wiener diversity index and ANOVA were used to analyze the wetland bird community structure. A total of 4337 individual birds belonging to 120 species, 15 orders, and 41 families were recorded. Among the identified bird species, the Abyssinian catbird, white-winged cliff chat, Abyssinian longclaw, wattled ibis, and black-winged lovebird are endemic and near-endemic species, which are found only in Ethiopia and Eritrea. The Passeriformes order had the greatest number of species (n = 68), followed by the Columbiformes order (n = 9). The​ Mai-Shigurti Wetland had the greatest abundance of birds (N = 2472), while the Hatsebo Wetland had the least (N = 936). A high abundance of birds was recorded during the wet season (N = 2805), and a low abundance was recorded during the dry season (N = 1532). A significant difference in the abundance of bird species was observed among wetlands and seasons (p<0.05). The highest species diversity (H′ = 4.13) was recorded in Mai-Shigurti during the wet season, whereas the lowest was recorded in Hatsebo during the dry season (H′ = 3.2). The highest species evenness was recorded in Hatsebo (E = 0.82) during the dry season, and the lowest was recorded in Mai-Shigurti (E = 0.72) during the wet season. The results show that wetlands support a high diversity of birds; however, they are highly threatened by anthropogenic threats, including solid waste disposal, erosion, agricultural expansion, human settlement, livestock overgrazing, military camping, and eucalyptus cultivation. Therefore, community-based conservation initiatives should be implemented to mitigate these threats. Moreover, wetland management policies should be established to safeguard wetlands and their biological resources.